The relationship between transfer of training on job performance among support staff at INTAN Sarawak/ Muhammad Yassir Dee - Dee, Muhammad Yassir (2019)
First and foremost, there is ambiguity in previous research that factor of transfer of training such as trainee characteristics, training design and work environment are associated with job performance. In this quantitative research a total of 59 support staff were taken from INTAN Sarawak as a sample and has found that most of the respondents are female and the respondents are mostly at the age ranging from 26-35, married and have a bachelor’s degree and most of them have working experience about 5-10 years. Normality analysis conducted verified that 59 data used were valid. Cronbach Alpha’s for training design variable which is the highest at 0.780 shows that the variable is acceptable as according to Salkind (2013) if the value of Cronbach Alpha’s above 0.7 it is considered as acceptable. This shows that training design is the most reliable variable in this study. The lowest Cronbach Alpha’s value is for work environment which is only 0.602 as it is still acceptable and reliable variable among trainee characteristics and training design. Training design is the most impactful towards their job performance. (mean=3.99, SD=0.36). The mean value of training design is very close to 4.00 as this proves that training design is the most superior variables compared with trainees characteristics and work environment. The highest value obtained by training design (r=.502,p>0.01) while work environment once again is the least factor of all variables (r=.237,p<0.01) and this value shows that work environment is not correlate and does not have any influence in transfer of training towards job performance.